Association between uterine leiomyoma with body mass index and parity in the women of coastal Karnataka, India - C., Amruta; Shetty, Annappa; Pawaskar, Naresh; Desai, Shreya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Fibroid is the commonest benign tumor of the uterus and also commonest benign solid tumor in females. Fibroids are found to be 2-3 times more prevalent in obese women, specially the one’s with central obesity and in those with BMI > or = 35. Epidemiologic data also shows pregnancy is associated with reduced risk of fibroids. So, the present study will be a cross-sectional study which will be undertaken to know the association of uterine leiomyoma with BMI and parity in the women of coastal Karnataka. Methods: An analytical cross-sectional study was performed among the 100 patients attending OPD at the department of obstetrics and gynecology, Karwar institute of medical sciences from June 2018 to August 2018. Women suspected to have fibroid based on their symptoms were made to undergo ultrasonography. Comparison was made between the parity, body mass index of the patient and the size of the uterine fibroid visualized. Results: Out of 100 women studied 63 were nulliparous and 37 women were multiparous. Incidence of fibroid is inversely proportional to parity. When BMI < 18 only 6 women had fibroid, when BMI > 25, 57 women had fibroids and between 18-25 group 37 women were diagnosed with fibroid. Conclusions: The fibroid showed directly proportional association with BMI. Greater the BMI, more was the risk of fibroids. The fibroid showed inversely proportional association with parity. Greater the parity of the women lesser was her chances of being at risk of having fibroid.